Brief Report: Association of HLA–DRB1*01 With IgA Vasculitis (Henoch‐Schönlein). Issue 3 (March 2015) - López‐Mejías, Raquel; Genre, Fernanda; Pérez, Belén Sevilla; Castañeda, Santos; Ortego‐Centeno, Norberto; Llorca, Javier; Ubilla, Begoña; Remuzgo‐Martínez, Sara; Mijares, Verónica; Pina, Trinitario; Calvo‐Río, Vanesa; Márquez, Ana; et al.
<x xml:space="preserve">Abstract</x> Objective IgA vasculitis (Henoch‐Schönlein) (IgAV), formerly called Henoch‐Schönlein purpura, is the most common vasculitis in children, but it is not rare in adults. Increased familial occurrence supports a genetic predisposition to IgAV. In this context, an association with the HLA–DRB1*01 phenotype has been suggested in Caucasian individuals with IgAV. However, data on the potential association of IgAV with HLA–DRB1*01 were based on small case series. We undertook this study to further investigate this potential association by performing HLA–DRB1 genotyping in the largest series of IgAV patients ever assessed for genetic studies in Caucasians. Methods We assessed 342 Spanish patients with IgAV as well as 303 controls matched for sex and ethnicity. IgAV patients were required to fulfill the classification criteria described by Michel et al as well as the American College of Rheumatology 1990 classification criteria. HLA–DRB1 alleles were determined using the polymerase chain reaction–sequence‐specific oligonucleotide probe method. Results We found a statistically significant increase in the frequency of the HLA–DRB1*01 phenotype in IgAV patients compared with controls (43% versus 27%; P < 0.001) (odds ratio 2.03 [95% confidence interval 1.43–2.87]). This was due to the increased frequency of the HLA–DRB1*0103 allele in IgAV patients compared with controls (14.3% versus 2.0%; P < 0.001) (odds ratio 8.27 [95% confidence interval 3.46–23.9]). These results remained statistically significant after Bonferroni adjustment. In contrast, a statistically significant decrease in the frequency of the HLA–DRB1*03 phenotype, due to the presence of the HLA–DRB1*0301 allele, was observed in IgAV patients compared with controls (5.6% versus 18.2%; P < 0.001) (odds ratio 0.26 [95% confidence interval 0.14–0.47]), even after Bonferroni adjustment. No association of HLA–DRB1 with specific features of the disease was found. Conclusion Our study confirms an association of IgAV with HLA–DRB1*01 in Caucasians. There also appears to be a protective effect against the development of IgAV in Caucasians carrying the HLA–DRB1*03 phenotype.